Deciphering the origin of small metal artefacts from Castillo de Huarmey (Peru) with Pb, Cu, and Ag isotopes. (28th March 2022) - Kałaska, Maciej; Mathur, Ryan; Kamenov, George; Chyla, Julia; Prządka‐Giersz, Patrycja; Giersz, Miłosz
Abstract: This paper presents Ag, Cu, and Pb isotopes for five silver and 10 copper artefacts found in the first intact pre‐Columbian tomb of the Wari culture female elite at Castillo de Huarmey, Peru. Ag and Cu isotope data indicate that the metals were extracted from primary, hypogene ore deposits. Most of the Pb isotope data for the Castillo de Huarmey artefacts correlate with the core Wari site of Conchopata, suggesting utilization of ores from similar deposits. The observed spread in Pb isotopes can be explained by the utilization of regional ores with highly variable Pb isotopes, such as the Julcani deposit. Alternatively, the linear nature of the Pb isotope results obtained for these samples may also be a result of the mixing of ores from different deposits or the re‐smelting of metals. Some of the Pb isotope results also indicate imports from other remote regions, providing evidence for long‐distance interactions on a vast regional scale, in the northern (North Coast of Peru) and southern (Southern Peru and Potosi region in Bolivia) spheres of influence of the Wari Empire and the Tiwanaku state.